Modern Music: A Concise History - Griffiths, Paul (Singapore Thames & Hudson, 1994)
Beginning at the threshold of the modern era, with the late Romanticism of Debussy and Mahler, the author traces the new directions of music through composers such as Alban Berg and Anton Webern, Charles Ives, Edgard Varese and Olivier Messiaen, Karlheinz Stockhausen, Pierre Boulez, Philip Glass and Elliott Carter. The various paths are made clear by a concentration on the major works and turningpoints in the music of our time: the new rhythmic force that came in with The Rite of Spring, the unbounded universe of Schoenberg's atonality, the undreamed-of possibilities opened up by electronics, the role of chance in the music of John Cage and the astonishing diversity of minimalism.
Keywords: 20th Century (1901-2000); Music history